2012
DOI: 10.1017/s1751731111001674
|View full text |Cite
|
Sign up to set email alerts
|

Expression and activities of hepatic cytochrome P450 (CYP1A, CYP2A and CYP2E1) in entire and castrated male pigs

Abstract: This study aimed to provide further insights into the mechanism of in vivo regulation of cytochrome P450 (CYP450) 1A, 2A and 2E1 activities in pigs with different levels of testicular steroids. Hepatic mRNA and protein expression and enzymatic activity of CYP1A, CYP2A and CYP2E1 were compared between entire male and castrated pigs. Castration was performed either surgically or immunologically. The pigs were divided into four groups. In the first group, piglets were surgically castrated without anaesthesia. Imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 27 publications
1
32
1
Order By: Relevance
“…This activity is not detectable in the porcine liver microsomes at the age of 1 day and 2 weeks of intact males, but detected at a significant level in castrated males at the age of 5 weeks, and then rapidly increases with growth. This is consistent with the significant increase in CYP2A mRNA expression, protein, and enzyme activity levels after removal of the primary androgen source (Gillberg et al ., ; Chen et al ., ; Zamaratskaia et al ., ; Brunius et al ., ) in addition to the age effect.…”
Section: Discussionmentioning
confidence: 98%
“…This activity is not detectable in the porcine liver microsomes at the age of 1 day and 2 weeks of intact males, but detected at a significant level in castrated males at the age of 5 weeks, and then rapidly increases with growth. This is consistent with the significant increase in CYP2A mRNA expression, protein, and enzyme activity levels after removal of the primary androgen source (Gillberg et al ., ; Chen et al ., ; Zamaratskaia et al ., ; Brunius et al ., ) in addition to the age effect.…”
Section: Discussionmentioning
confidence: 98%
“…In immunocastrates with an overall high feed intake rate significantly higher indole concentrations were measured than in all other groups. It is known that the levels of enzymes that are involved in the degradation of skatole (CYP2E1 and CYP2A) are increased in barrows and immunocastrates when compared with the levels in boars (Zamaratskaia et al, 2009;Brunius et al, 2012). In vitro studies with porcine hepatocytes revealed that the addition of androstenone in physiological amounts reduced the activity of both enzymes (Doran et al, 2002b;Rasmussen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Kojima et al [8] showed that administration of testosterone propionate to pigs decreased the expression of CYP1A. The suggestion that CYP450 expression in pigs is affected by steroids is further supported by studies showing difference in CYP450 expression/activity with respect to gender [9][10][11][12][13], castration [14] and immunocastration (active immunization against GnRH) [11,15]. These studies provide strong evidence that androgens and estrogens have a down-regulating effect on CYP450 expression and activity.…”
Section: Introductionmentioning
confidence: 93%